The potential value of fibrinogen-to-albumin ratio in assessing disease activity in rheumatoid arthritis - Li, Xiaoli; Shen, Jingfang; Leng, Lina; Han, Yaorong; Zhang, Jinfeng; Li, Lianju; Qiao, Yuhua (Frontiers in Immunology, 2025)
BackgroundThe fibrinogen-to-albumin ratio (FAR) has emerged as a promising inflammatory marker, but its relationship with rheumatoid arthritis (RA) disease activity remains unclear. This study sought to elucidate the association between FAR and RA disease activity and to assess its potential for identifying high disease activity states.MethodsWe conducted a cross-sectional study of 1,191 consecutive RA inpatients at Xingtai People’s Hospital from March 2022 to December 2024. FAR was calculated as fibrinogen (g/L) divided by albumin (g/L). Disease activity was assessed using the 28-joint Disease Activity Score (DAS28) based on C-reactive protein (DAS28-CRP) and erythrocyte sedimentation rate (DAS28-ESR). Multiple linear regression and generalized additive models were employed to examine the association of FAR with disease activity. Receiver operating characteristic (ROC) analysis evaluated FAR’s discriminatory performance for high disease activity.ResultsAfter exclusions, 981 patients (mean age, 57.7 years; 77.9% female) were included; 95.6% had moderate-to-high disease activity. A significant nonlinear association between FAR and disease activity was detected, with a saturation threshold at FAR = 0.14. Below this threshold, FAR was strongly and positively associated with DAS28-ESR [β = 15.21; 95% confidence interval (CI), 13.01–17.42] and DAS28-CRP (β = 13.07; 95% CI, 11.07–15.07). Above the threshold, associations were substantially attenuated and not statistically significant (DAS28-ESR: β = 2.19; 95% CI, −1.53–5.92; DAS28-CRP: β = 3.37; 95% CI, −0.01–6.74). Furthermore, FAR demonstrated good discriminatory ability between high and moderate disease activity, with area under the curve (AUC) values of 0.80 for DAS28-ESR and 0.81 for DAS28-CRP.ConclusionThis study identified a nonlinear relationship between FAR and RA disease activity in inpatients with predominantly moderate-to-high disease activity, characterized by a saturation threshold effect. FAR showed good discriminatory ability for distinguishing high from moderate disease activity. These findings suggest that FAR may serve as a promising and readily accessible inflammatory marker to complement existing assessments of disease activity. However, multicenter validation is warranted.